Polychlorinated Biphenyl Exposure Alters tRNA Transcriptome in High-Fat Diet-Fed Mouse Liver - Carolyn M. Klinge; Julia H. Chariker; Kellianne M. Piell; Belinda J. Petri; Eric C. Rouchka; Matthew C. Cave (Non-Coding RNA, 2025)
Background/Objectives: Exposure of high-fat diet (HFD)-fed mice to polychlorinated biphenyls (PCBs) results in metabolic dysfunction-associated steatotic liver disease (MASLD) and progression to metabolic dysfunction-associated steatohepatitis (MASH). The mechanisms by which HFD diet and PCBs increase MASLD are unclear. Previously, we identified differences in HFD-fed mouse liver tRNA modifications with single oral exposures to the dioxin-like PCB126, the non-dioxin-like PCB mixture Aroclor 1260 (Ar1260), or the combination of Ar1260 + PCB126. Methods: Here, we used small RNA sequencing and the tRNA analysis of expression (tRAX) pipeline to examine if PCB exposures alter the tRNA transcriptome, including tRNA-derived fragments (tRFs), in the livers of the PCB-exposed mice. Results: Each PCB exposure produced distinct hepatic tRNA transcriptomes with more tRNAs decreased than increased. Only tRNA-Glu-TTC-1 was reduced with all three PCB exposures. More changes in tRFs were identified with Ar1260 alone or in combination with PCB126 than with PCB126 alone. Four tRF-3s were upregulated in both PCB126 and Ar1260 + PCB126 co-exposed mice, suggesting PCB126 as responsible for this increase. We previously reported that PCB126 exposure increased hepatic Angiogenin (ANG) protein which generates tRF-3s. Four previously reported tRNA modifications corresponded to positions of PCB-associated tRNA modifications identified by tRAX: m1A, m6A, ms2t6A, and Ψ. Conclusions: Overall, the differences in hepatic tRNAs and tRFs with three different PCB exposures suggest that PCB exposures play an unexplored role in regulating translation in mouse liver.